2023
DOI: 10.3349/ymj.2022.0342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mesenchymal Stem Cells Treatment on Radiation-Induced Proctitis in Rats

Abstract: Purpose There are no effective treatment methods with which to control complications of radiation proctitis with fistula or recurrent bleeding following radiation treatment for prostate, cervical, or rectal cancer. Mesenchymal stem cells (MSCs) can induce immune modification, resulting in tissue repair and regeneration. Therefore, we used a rat model of radiation-induced proctitis and observed the effects of using human placenta-derived (PD) and adipose tissue-derived (AD) MSCs. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The upregulation of Sox6, Col2a1, and Agc1 expression in a murine model of bronchopleural fistula may be associated, respectively, with stem cell activation and differentiation, modulation of the inflammatory response, and increased proteolytic activity in tissue remodeling 42 . In a rat model study of radiation-induced proctitis, the injection of ASC demonstrated reduction in fibrosis and an increase in proliferation, aligning with our findings 43 . The Ki-67 stain revealed a higher presence of proliferative cells in the ASC injection groups, suggesting its potential to support epithelial regeneration.…”
Section: Discussionsupporting
confidence: 90%
“…The upregulation of Sox6, Col2a1, and Agc1 expression in a murine model of bronchopleural fistula may be associated, respectively, with stem cell activation and differentiation, modulation of the inflammatory response, and increased proteolytic activity in tissue remodeling 42 . In a rat model study of radiation-induced proctitis, the injection of ASC demonstrated reduction in fibrosis and an increase in proliferation, aligning with our findings 43 . The Ki-67 stain revealed a higher presence of proliferative cells in the ASC injection groups, suggesting its potential to support epithelial regeneration.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, irradiation enhances the internalization of MSC-derived extracellular vehicles (Evs) in epithelial cells, and MSC-derived EV treatment can improve small intestinal epithelial renewal by stimulating the proliferation of epithelial crypt cells and inhibiting apoptosis [ 115 ]. Kim et al [ 116 ] established a rat model of radiation-induced proctitis to investigate the therapeutic effects of human placenta-derived (PD) and adipose tissue-derived (AD) MSCs. They found that compared to the control group, both types of MSCs reduced rectal fibrosis, promoted mucosal proliferation, and inhibited apoptosis.…”
Section: Treatment Strategy Of Radiation-induced Intestinal Injurymentioning
confidence: 99%